Nomogram Predicting Parametrial Involvement Based on the Radical Hysterectomy Specimens in the Early-Stage Cervical Cancer - Li, Chunbo; Yang, Shimin; Hua, Keqin (Frontiers in Surgery, 2021)
Objective: Radical hysterectomy (RH) is the surgical standards for the treatment of early-stage cervical cancer (CC). However, this procedure is associated with a high rate of adverse impact on the quality of patient life. Since the rate of parametrial involvement (PI) is low for patients with early-stage CC, some authors believe that patients with early-stage CC may benefit from less radical surgery. This study aims to estimate the incidence of PI in patients with early-stage CC and establish a simple nomogram to identify patients with low risk of PI who may benefit from less radical surgery. Methods: All patients who underwent RH and pelvic lymphadenectomy were included. The significant independent predictors were identified through Cox regression analysis and then incorporated into a nomogram to predicate PI. The calibration plots and receiver operating characteristic (ROC) curves were estimated to assess the predictive accuracy of the nomogram. Results: 4533 patients met the inclusion criteria and 441 women (9.7%) had PI. The positive PI rate in less than equal to 2 cm group (1.2%) was significantly lower than in greater than 2-less than equal to 4 cm (6.2%) or greater than 4 cm (22.4%) groups. Multivariate analyses revealed that tumor size (P=0.002), lymph vascular space invasion (LVSI) (P=0.001), vaginal involvement (VI) (P<0.001), statue of pelvic lymph nodes (PLN) (P=0.001), and depth of stromal invasive (DSI) (P<0.001), were independent prognostic factors of PI. Finally, five variables were combined to construct nomogram model. The concordance indexes (C-indexes) of PI were 0.756 (95% CI, 0.726-0.786) for the training validation and 0.729 (95% CI, 0.678-0.780) for the testing validation. Calibration plots further showed good consistency between the nomogram prediction and actual observation. Conclusions: Our finding confirmed that patients with tumor size 2 cm or smaller were at very low risk for PI. If other variables such as negative LVSI, DSI < 50%, no VI and negative PLN was limited, the risk would reduce significantly. Meanwhile, a simple nomogram based on significant clinicopathological characteristics could be used as a tool for clinicians to predict PI among early-stage CC patients, who might benefit a less radical surgery.